Single Intra-Articular Platelet-Rich Growth Factor Injection for Knee Osteoarthritis: Is It Effective in Severe Patients? - Wiwattanawarang, Nuttawut (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: This study evaluated the clinical outcomes of intra-articular (IA) platelet-rich growth factor (PRGF) in patients with varying severities of knee osteoarthritis (KOA) using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score. It also examined whether IA PRGF could delay or prevent surgical intervention in patients with severe KOA. Methods: In this analytical observational cohort study, 120 patients with KOA, without systemic inflammatory disease or other intra-articular lesions, were classified using the Kellgren-Lawrence (KL) grading system. PRGF, a combination of leukocyte-rich platelet-rich plasma (LR-PRP) and injectable platelet-rich fibrin (iPRF), was prepared using the PP, GF, and ALPAS systems. A single 7 mL IA PRGF injection was administered. WOMAC scores were assessed at baseline, 1 week, and 1, 3, 6, and 12 months post-injection. Results: Ninety-six female and 21 male patients (mean age: 64.9±8.3 years) were included. Based on KL grading, 38 patients were classified as mild (grade I-II), 44 as moderate (grade III), and 35 as severe (grade IV). All groups showed a decline in WOMAC scores after PRGF injection. Although baseline scores were highest in the severe group, the pattern of score reduction was similar across all severities. WOMAC scores at 3 months were lower in the mild and moderate groups than in the severe group. At 12 months, all groups maintained significantly reduced scores compared to baseline. Conclusions: A single IA PRGF injection effectively improves pain, stiffness, and function in patients with severe KOA, with outcomes comparable to those in mild and moderate cases over 12 months of follow-up.